Perioperative Beta Blockade - Irani, Jennifer Lynn (Clinics in Colon and Rectal Surgery, 2013)
The use of preoperative beta (β) blockade has been through several changes, and it is clear that large, randomized controlled trials on the subject are in need. Currently, a judicious approach to perioperative β blockade is supported. Continuation of β blockers is recommended for the patient taking them prior to surgery. Patients undergoing large colorectal procedures, with coronary artery disease or high cardiac risk, should have β blockers titrated to heart rate and blood pressure. Dosages should be titrated to heart rate and blood pressure rather than using fixed, long-acting dosages. When β blockers are indicated, they should be initiated weeks before surgery.
Keywords: β blockers; perioperative; coronary artery disease; colon and rectal surgery